Galex and optical observations of GW librae during the long decline from superoutburst - Bullock, E.; Szkody, P.; Mukadam, A.; Borges, B.; Fraga, L.; Gänsicke, B.; Harrison, T.; Henden, A.; Holtzman, J.; Howell, S.; Lawson, W.; Levine, S.; et al. (Institute of Physics Publishing, 2011)
The prototype of accreting, pulsating white dwarfs (GW Lib) underwent a large amplitude dwarf nova outburst in 2007. We used ultraviolet data from Galaxy Evolution Explorer and ground-based optical photometry and spectroscopy to follow GW Lib for three years following this outburst. Several variations are apparent during this interval. The optical shows a superhump modulation in the months following outburst, while a 19 minute quasi-periodic modulation lasting for several months is apparent in the year after outburst. A long timescale (about 4 hr) modulation first appears in the UV a year after outburst and increases in amplitude in the following years. This variation also appears in the optical two years after outburst but is not in phase with the UV. The pre-outburst pulsations are not yet visible after three years, likely indicating the white dwarf has not returned to its quiescent state.